Interoceptive awareness mediates the relationship between anxiety and the intensity of unpleasant feelings - Pollatos, Olga; Traut-Mattausch, Eva; Schroeder, Heike; Schandry, Rainer (Journal of anxiety disorders, 2007)
This study examined the relationship between interoceptive awareness, anxiety, and the intensity of unpleasant feelings. The perception of visceral signals (interoceptive awareness) plays an important role in the pathophysiology of anxiety disorders. Nevertheless, studies simultaneously investigating relationships between emotion processing, anxiety, and interoceptive awareness remain sparse. The present study was designed to elucidate the interrelations between these variables. Trait anxiety and interoceptive awareness were assessed in 102 healthy participants. Following this, neutral and unpleasant pictures were presented and subjects were asked to rate perceived emotional pleasantness and arousal. We found that both interoceptive awareness and trait anxiety were significantly positively correlated with mean arousal scores for unpleasant pictures. A positive relationship between interoceptive awareness and trait anxiety was also found. Subsequent regression analyses showed that the relationship between emotional arousal and trait anxiety was mediated by differences in interoceptive awareness. Our results highlight the possible role of interoceptive awareness in the development of trait anxiety and may have further implications for theoretical models of anxiety disorders and their treatment.